Plastic multilayered closure versus orthopedic surgeon closure after spinal instrumentation in pediatric neuromuscular scoliosis. Issue 1 (15th February 2023) - Ezeokoli, Ekene U; Tamma, Poornima L; Borici, Neritan; Inneh, Ifeoma; Buchanan, Edward P; Smith, Brian G
Abstract : Objective: To compare wound complication rates between orthopedic closure (OC) and plastic multilayered closure (PMC) in patients undergoing primary posterior spinal fusion for neuromuscular scoliosis (NMS). We hypothesize that multilayered closure will be associated with better postoperative outcomes. Methods: We collected data on pediatric patients diagnosed with NMS who underwent first time spinal instrumentation between 1 January 2018 and 31 May 2021. Patient demographics, length of surgery, spinal levels fused and operative variables, wound complication rate, treatments, and need for wound washout were reviewed in depth and recorded. Results: In total, 86 patients were reviewed: 46 with OC and 40 with PMC. There was a significant increase in operating room (OR) time with PMC compared with OC (6.7±1.2 vs 7.3±1.3, p=0.016). There was no difference in complication rate, mean postoperative day of complication or unplanned return to the OR for OC and PMC, respectively. There was a slightly significant increase in the number of patients going home with a drain in the PMC cohort compared with the OC cohort (2.1% vs 15%, p=0.046). Conclusions: PMC demonstrated longer OR times than OC and did not demonstrate a statistically significant reduction in wound complications or unplanned returns to the OR. However, other studies have demonstrated statistical and clinical significance with these variables. Surgical programs should review internal patient volumes and outcomes for spinal fusion in NMS patients and consider if PMC after spinal fusions in pediatric patients with NMS or other scoliosis subtypes is an appropriate option in their institution to minimize postoperative wound complications.